2009
DOI: 10.1108/10748120910998425
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding engagement in games: an eye‐tracking study

Abstract: Dr Tony Renshaw has been involved in research and consultancy using eyetracking and holds a PhD in this area. He has been responsible for the development of new and improved eyetracking metrics. Tony graduated from Loughborough University in Chemistry and Management Studies and has held a variety of senior positions within REACT Centre Limited and the Services Division of ICL. He is now Director of Usability North at Leeds Metropolitan University. Richard StevensRichard Stevens is a Senior Lecturer and Teacher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 8 publications
0
22
0
3
Order By: Relevance
“…For example, several prominent reviews of the engagement literature with sections focusing on measurement including Fredricks et al (2004) and Jimerson, Campos, and Greif (2003) do not mention selfpaced reading or eye-movement data. However, some programs of research related to science instruction such as computer tutoring and educational game design (Renshaw, Stevens, & Denton, 2009) have embraced these methods.…”
Section: Self-paced Reading and Eye-tracking Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, several prominent reviews of the engagement literature with sections focusing on measurement including Fredricks et al (2004) and Jimerson, Campos, and Greif (2003) do not mention selfpaced reading or eye-movement data. However, some programs of research related to science instruction such as computer tutoring and educational game design (Renshaw, Stevens, & Denton, 2009) have embraced these methods.…”
Section: Self-paced Reading and Eye-tracking Methodsmentioning
confidence: 98%
“…This finding has contributed to the wide use of eye-tracking technology in marketing research (Pieters & Wedel, 2004). In research on computer game design, Renshaw et al (2009) found that certain eye movements were associated with dissatisfaction. Jennett et al (2008) found that immersion in a game was associated with fewer but longer fixations.…”
Section: Assumption 3-like More Look Morementioning
confidence: 93%
“…Com relação ao uso do eye tracking para medição direta da satisfação, foi verificado que muitos artigos utilizam o eye tracking em testes de usabilidade apenas para medir eficiência e satisfação, ou outros dados relativos à cognição, interesse visual e atenção mas continuam usando questionários para medir a satisfação, especificamente (CASTILLA et al, 2015;BAHARUM & JAAFAR, 2014;CHENG & LIU, 2011;SI-MUNICH, ROBINS & KELLY, 2015;RENSHAW, STEVENS & DENTON, 2009;GUO et al, 2016). Alguns dos artigos buscam fazer algumas inferências a partir dos resultados do eye tracking referente a algumas medições mais subjetivas como engajamento Em alguns dos artigos pesquisados, existe uma preocupação em obter dados quantitativos para a medida da satisfação.…”
Section: Análise Do Conteúdo Dos Artigos Selecionadosunclassified
“…We may say that of learning too, of course, which draws again attention to the question of whether engagement takes place as a series of actions over time, or is a qualitative aspect of a specific experience. When studying games, researchers have also used physiological techniques such as analysis of facial expressions and body language (Hughey, 2002), measurement of physiological factors such as heart rate and brain activity (Nacke & Lindley, 2008), and tracking of eye movements (Jennett et al, 2008;Renshaw et al, 2009). Objective measures, such as frameworks for evaluation of activities (Sweetser & Wyeth, 2005), observations (Read, MacFarlane, & Casey, 2002), game metrics such as frequency and duration (Ronimus, Kujala, Tolvanen, & Lyytinen, 2014), and voluntary time on task (Ronimus et al, 2014;Virvou, Katsionis, & Manos, 2004) have also been used.…”
Section: Measuring Engagementmentioning
confidence: 99%